QUALITY OF SHRIMP CRACKERS WITH ADDITIONAL INGREDIENTS OF BLUE SWIMMING CRAB (Portunus pelagicus) WASTE PRODUCT, LEMI - Jumiati Jumiati; Yuyun Suprapti (Jurusan Perikanan dan Kelautan, 2023)
The purpose of this study was to determine the difference in the quality of crabs from the addition of crab mustard in the manufacture of shrimp crackers, increasing the usefulness of crab mustard which are generally discarded and can be used as processed cracker products. The use of crab mustard in this study as an additional ingredient in the manufacture of shrimp crackers. Quality parameters in the form of nutritional composition include: protein, fat, carbohydrate, water and ash, organoleptic test (texture, taste, smell and color) and Total Plate Count (TPC). Experimental method, analysis of data by F test on product quality with 5 treatment composition comparisons: flour, mustard and shrimp meat, namely: L (50%: 50%:0%); A (50% : 37.5% : 12.5%); B (50% : 25% : 25%); C (50% : 12.5% : 37.5%); U (50% : 0% : 50%), each treatment had 3 replications. The results of proximate analysis (protein, fat, carbohydrates, water and ash), organoleptic test showed a very significant difference (P<0.01) between treatments, but for TPC there was no significant difference (P>0.05). The best nutritional composition in treatment C. The best organoleptic test results in treatment C. The best TPC value in treatment A.